TINJAUAN YURIDIS PENEGAKAN HUKUM DI LAUT TERHADAP PENGUNGSI ROHINGYA DI INDONESIA - panjaitan, edward; Waruwu, Rebecca C; Sofiano, Ramazan B; Zila, Catherine Irene; Sitorus, Matthew N (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The Rohingya refugee crisis in the Asia Pacific has posed challenges for Indonesia, particularly in managing maritime refugees arriving in its territorial waters. The surge in the number of Rohingya refugees fleeing from the refugee camps in Cox's Bazar, Bangladesh, has triggered an influx into Indonesia, driven by the unsafe and deteriorating humanitarian conditions in Myanmar. Rohingya refugees embark on perilous sea voyages using small boats, often with the assistance of smugglers. These journeys involve security, safety, and exploitation risks. This situation has triggered a surge in refugee arrivals in Indonesia's territorial waters, challenging the capacity of maritime authorities to handle this complex and risk-laden situation. Indonesia's maritime security agencies, such as the Maritime Security Agency (Bakamla) and the Indonesian Navy (TNI AL), play crucial roles in maintaining maritime security and safety. Bakamla is responsible for maintaining maritime stability, security, and law enforcement, while the TNI AL has the primary task of safeguarding the sovereignty and territorial integrity of Indonesia. These two agencies synergize in addressing the Rohingya refugee crisis. Indonesia, guided by humanitarian principles and adherence to international law, has accepted Rohingya refugees. The management of this crisis is conducted in compliance with applicable legal provisions and upholding humanitarian values. However, several challenges arise regarding the legal framework in Indonesia's maritime domain in handling Rohingya refugees, particularly in the context of the authority and roles of relevant agencies and efforts to prevent human trafficking (TPPO). Additionally, it is crucial to avoid violations of the non-refoulement principle in managing Rohingya refugees arriving in Indonesia's territorial waters, considering Indonesia's obligations to uphold international law and humanitarian norms.